1997
DOI: 10.1093/emboj/16.9.2352
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal mesoderm patterning in mouse embryos mutant for the SH2 tyrosine phosphatase Shp-2

Abstract: Shp‐1, Shp‐2 and corkscrew comprise a small family of cytoplasmic tyrosine phosphatases that possess two tandem SH2 domains. To investigate the biological functions of Shp‐2, a targeted mutation has been introduced into the murine Shp‐2 gene, which results in an internal deletion of residues 46–110 in the N‐terminal SH2 domain. Shp‐2 is required for embryonic development, as mice homozygous for the mutant allele die in utero at mid‐gestation. The Shp‐2 mutant embryos fail to gastrulate properly as evidenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
412
1
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(443 citation statements)
references
References 68 publications
27
412
1
3
Order By: Relevance
“…Saxton et al (1997) found that murine ®broblasts carrying a mutated version of SHP-2, lacking the aminoterminal SH2 domain and with a non-functional carboxyterminal SH2 domain, responded to PDGF-BB with increased MAP kinase activation compared to wild-type cells, consistent with a negative control function of SHP-2 in PDGFmediated activation of MAP kinase. However, these data di er from ®ndings by Lu et al (1998), who showed a decreased PDGF-induced MAP kinase activity in SV40 large T immortalized ®broblasts, expressing an identically mutated SHP-2; however, the interpretation is complicated by the fact that the immortalized ®broblasts carrying the SHP-2 mutation express dramatically lower levels of PDGF b-receptor than wild-type cells .…”
Section: Discussionmentioning
confidence: 75%
“…Saxton et al (1997) found that murine ®broblasts carrying a mutated version of SHP-2, lacking the aminoterminal SH2 domain and with a non-functional carboxyterminal SH2 domain, responded to PDGF-BB with increased MAP kinase activation compared to wild-type cells, consistent with a negative control function of SHP-2 in PDGFmediated activation of MAP kinase. However, these data di er from ®ndings by Lu et al (1998), who showed a decreased PDGF-induced MAP kinase activity in SV40 large T immortalized ®broblasts, expressing an identically mutated SHP-2; however, the interpretation is complicated by the fact that the immortalized ®broblasts carrying the SHP-2 mutation express dramatically lower levels of PDGF b-receptor than wild-type cells .…”
Section: Discussionmentioning
confidence: 75%
“…SIRPa1 overexpression in NIH3T3 cells inhibited DNA synthesis and MAPK phosphorylation following EGF or insulin stimulation (Kharitonenkov et al, 1997). Genetic and biochemical studies have shown that SHP2 may positively regulate MAPK signaling in response to insulin, FGF, and EGF (Noguchi et al, 1994;Tang et al, 1995;Bennett et al, 1996;Saxton et al, 1997;Deb et al, 1998;Shi et al, 1998), but attenuate MAPK activation following PDGF and neuregulin stimulation (Saxton et al, 1997;Tanowitz et al, 1999). In other studies, increased SHPS-1/SHP2 complex formation resulting from overexpression of SHPS-1 potentiated the RAS-MAPK pathway in response to insulin or integrin stimulation (Oh et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…In vivo studies of genetically inactivated SHP-2 in primary, mature T cells have been impossible so far, because genetic inactivation of SHP-2 results in embryonic lethality around day 10.5 with defects in gastrulation and mesoderm development [7,8]. However, there is evidence for a role of SHP-2 in distinct signaling cascades in hematopoietic cells from in vitro differentiation of SHP-2-deficient ES cells and the generation of chimeric mice.…”
Section: Introductionmentioning
confidence: 99%